IP over WDM network - Shum, Ping (2008)
With the recent evolution of Internet and telecommunication networks, "IP over WDM networks" has emerged as a promising architecture for next generation networks. Only few works have been done on chaotic optical communication using dual ring fiber laser configuration as well as the blocking performance evaluation of label switched path (LSP) establishment in IP/MPLS over optical networks. This work investigates an all-optical IP-over-WDM network with strong built in security. Chaotic optical communication, especially chaotic signal generation, and connection establishment of LSP in the IP/MPLS over optical networks, are considered in a holistic manner.